Halal Tourism Model Based On Local Wisdom In Bukit Lawang As One Of The Branding Efforts Towards Excellent Primadona North Sumatra - Harianja, Pantun (International Journal of Science, Technology & Management, 2022)
The purpose of this research is to find a model of amenity formulation, word of mounth and halal knowledge on halal tourism brand image and tourist satisfaction. The method of analysis in the first year in this study used the approach SEM (Structural Equation Modeling) in building the concept of attractiveness, accessibility and tourism awareness in increasing tourist loyalty through out-of-school education. While in the second year, namely the application of a youth-based out-of-school education model in creating a Tangkahan brand image to be excellent in North Sumatra. The results of the study show that 1) Direct amenity has a positive influence and significant to the brand image in Bukit Lawang. 2) Directly the word of Mount has a positive and insignificant effect on the brand image of Bukit Lawang. 3) Halal knowledge has a positive influence and significant effect on tourist satisfaction in Bukit Lawang. 4) A mentality directly has a positive influence and significant effect on tourist satisfaction in Bukit Lawang. 5) Directly the word of Mount has a positive and insignificant effect on tourist satisfaction in Bukit Lawang. 6) Halal knowledge directly has a positive and positive effect significant effect on tourist satisfaction in Bukit Lawang. 7) Indirectly brand image has a significant role in mediating amenity to tourist satisfaction in Bukit Lawang. 8) Indirectly brand image has a significant role in mediating the word of mounth on tourist satisfaction in Bukit Lawang. 9) Indirectly brand image has a significant role in mediating halal knowledge on tourist satisfaction in Bukit Lawang.